2008
DOI: 10.1177/0748233708089004
|View full text |Cite
|
Sign up to set email alerts
|

A study of the teratogenic and fetotoxic effects of large doses of barbital, hexobarbital and butobarbital used for suicide attempts by pregnant women

Abstract: The teratogenic potential of barbiturates is debated. The objective of this study was to evaluate the effects of very large doses of different barbiturates, except phenobarbital and amobarbital, on fetal development in pregnant women who attempted suicide. These self-poisoned pregnant women were identified among the patients of the Department of Toxicology Internal Medicine, Korányi Hospital, Budapest. The prevalence at birth of congenital abnormalities and intrauterine fetal growth, based on pregnancy age at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…The majority of studies that have assessed the impact of suicidal ideation during pregnancy on fetal development have done so in the context of self-poisoning. A series of 15 articles were published from the Budapest Monitoring System of Self-Poisoning Pregnant Women that evaluated the potential effects of large doses of drugs on fetal development among pregnant women who attempted suicide (Czeizel et al, 1997, Czeizel et al, 1999, Timmermann et al, 2009, Gidai et al, 2008c, Gidai et al, 2008a, Gidai et al, 2008d, Gidai et al, 2008b, Gidai et al, 2010, Petik et al, 2008a, Petik et al, 2008b, Petik et al, 2012, Timmermann et al, 2008b, Timmermann et al, 2008a, Timmermann et al, 2008c). With regards to congenital anomalies, the primary outcomes of these studies, no statistically significant associations were reported with self-poisoning (Czeizel et al, 1997, Czeizel et al, 1999, Timmermann et al, 2009, Gidai et al, 2008c, Gidai et al, 2008a, Gidai et al, 2008d, Gidai et al, 2008b, Gidai et al, 2010, Petik et al, 2008a, Petik et al, 2008b, Petik et al, 2012, Timmermann et al, 2008b, Timmermann et al, 2008a, Timmermann et al, 2008c).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies that have assessed the impact of suicidal ideation during pregnancy on fetal development have done so in the context of self-poisoning. A series of 15 articles were published from the Budapest Monitoring System of Self-Poisoning Pregnant Women that evaluated the potential effects of large doses of drugs on fetal development among pregnant women who attempted suicide (Czeizel et al, 1997, Czeizel et al, 1999, Timmermann et al, 2009, Gidai et al, 2008c, Gidai et al, 2008a, Gidai et al, 2008d, Gidai et al, 2008b, Gidai et al, 2010, Petik et al, 2008a, Petik et al, 2008b, Petik et al, 2012, Timmermann et al, 2008b, Timmermann et al, 2008a, Timmermann et al, 2008c). With regards to congenital anomalies, the primary outcomes of these studies, no statistically significant associations were reported with self-poisoning (Czeizel et al, 1997, Czeizel et al, 1999, Timmermann et al, 2009, Gidai et al, 2008c, Gidai et al, 2008a, Gidai et al, 2008d, Gidai et al, 2008b, Gidai et al, 2010, Petik et al, 2008a, Petik et al, 2008b, Petik et al, 2012, Timmermann et al, 2008b, Timmermann et al, 2008a, Timmermann et al, 2008c).…”
Section: Resultsmentioning
confidence: 99%
“…69 Moreover, despite the use of barbiturates being progressively decreased in both neurological and psychiatric practice, such medications are still used by suicidal pregnant women. 70 The period of pregnancy at highest risk of suicide attempts seems to be the second trimester. 71 …”
Section: Resultsmentioning
confidence: 99%
“…Others have published studies on adverse outcomes associated with suicidal behaviour during pregnancy. [6][7][8][9][10][11]13 However, there has been little focus on infant outcomes besides congenital abnormalities, and the results have been mixed. 7,9,10 In our study, after taking into account a comprehensive list of potential confounders including psychiatric disorders, we found that women with suicidal behaviour had 1.3-fold to 1.4-fold increased odds of experiencing adverse infant outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Knowledge about the epidemiology of suicidal behaviour during pregnancy, including the causes and consequences of suicidal behaviour, is critical to inform suicide prevention strategies for pregnant women, and ultimately to reduce maternal mortality. 5 Although suicidal behaviour in pregnancy has been studied for decades, very few studies [6][7][8][9][10][11][12][13] have provided information on the associations of antepartum suicidal behaviour with infant and obstetric outcomes. 10,12 The majority of past studies have focused on suicide attempt by drug overdose.…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation